Welfare states and immigrant rights the politics of inclusion and exclusion - Sainsbury, Diane (Oxford : Oxford University Press, 2012)
'Welfare States and Immigrant Rights' deals with the policies and politics of immigrants' inclusion and exclusion in six countries representing different types of welfare states: the United States, the United Kingdom, Germany, France, Sweden, and Denmark.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Immigrants -- Civil rights; Immigrants -- Government policy; Welfare state -- Political aspects; Social integration -- Political aspects